PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERTAMBANGAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Vinni Alpionita; Kasmawati Kasmawati (Jurnal Riset Manajemen Indonesia, 2020)
This research was conducted with the aim to examine the effect of current ratio on profit growth in the coal subsector mining companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The independent variables used in this study are the current ratio and debt to equity ratio, while the dependent variable is earnings growth. In this study using secondary data obtained through the official website of the Indonesia Stock Exchange www.idx.co.id The research sample is a coal company. The sampling method used was purposive sampling to obtain a sample of 21 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows.. The results showed that the effect of the current ratio and debt to equity ratio simultaneously had a significant effect on earnings growth. While partially the effect of the current ratio has a significant effect on earnings growth, while the debt to equity ratio does not have a significant effect on earnings growth.